An investigation of the effects of helminth worm infection on the capacity of HIV vaccines to boost vaccine-generated immune responses - Humby, Samantha A (Division of Virology, 2017)
To protect against sexual transmission, successful future HIV vaccines will likely be given to adolescents as a booster subsequent to primary immunization during infancy. In sub-Saharan Africa (SSA), a large proportion of children are chronically infected with a variety of helminths. These infections may suppress the ability of a host to elicit vaccine-induced Th1 responses that are considered important for a successful HIV vaccine. This study investigated the effect of chronic helminthic infection on the boosting capacity of a poxvirus-protein HIV vaccine regimen (SAAVI MVA-C and Env gp140 protein) in a mouse model. Groups of mice were prime-vaccinated with SAAVI MVA-C through an intramuscular injection, and Env gp140 protein formulated in Alum adjuvant which was administered via an intraperitoneal injection. These vaccinations were given concurrently, 2 weeks prior to infection with Schistosoma mansoni (Sm) through a percutaneous route. Control mice were either left uninfected (Naïve) or infected in the same manner (Sm) without vaccination. A booster vaccination was given 8 weeks post helminth infection. HIV-specific immune responses were analysed in the blood and spleens two weeks after booster vaccination. The magnitudes of cumulative IFN-γ ELISPOT responses to HIV Gag, RT and Env peptides were significantly (p<0.05) lower in the vaccinated and Sm-infected (Vaccine+Sm) mice (948 sfu/106) than vaccinated and uninfected (Vaccine) mice (1733 sfu/106), with IFN-γ responses to RT (CD8) being the most dominant for both mouse groups (Vaccine+Sm: 734 ± 221 sfu/106, Vaccine: 521 ± 116 sfu/106). No significant difference was observed in the magnitudes of cumulative IL-2 ELISPOT responses to the vaccine peptides between the Vaccine+Sm and Vaccine groups, however IL-2-producing T cell responses to Env (CD4) dominated in both mouse groups. Vaccine+Sm and Sm groups had similar IFN-γ- and IL-2-producing T cell responses to SEA. Splenocytes from Vaccine+Sm mice secreted less Th1 (IFN-γ, IL-2, TNF- α) and Th2 (IL-4, IL-6, IL-10) cytokines than those from uninfected vaccinated mice in response to HIV vaccine peptides. The total number of activated CD4+ T cells responding to vaccine peptides was greater for Vaccine+ Sm mice than Vaccine mice (p<0.05), however, no such statistical significance was observed in the differences seen between these vaccinated mouse groups for the number of activated CD8+ T cells. The frequencies of central memory activated CD4+ T cells were seen to be greater in Vaccine group (Gag; 34.28 ± 8.35%, Pol; 33.53 ± 6.34%, Env(CD4); 33.92 ± 3.87%, Env (CD8); 38.76 ± 10.52%) as opposed to the Vaccine+Sm group (Gag; 28.09 ± 3.95%, Pol; 26.45 ± 4.66%, Env (CD4); 28.79 ± 6.95%, Env (CD8); 28.65 ± 3.29%). Furthermore, Vaccine+Sm mice had higher titres of HIV-1 gp140- specific IgG1 antibodies (p<0.0001) (a Th2 antibody marker) but significantly less gp140- specific IgG2a (p<0.0001) and IgG2b (p<0.001) (Th1 antibody markers) antibodies. This trend was also observed with total non-Env-specific antibody titres. This study demonstrates that chronic helminthic infection is associated with an attenuated boosting capacity of a poxvirus-protein HIV vaccine in a mouse model, suppressing both T cell cytokine production and Th1-type antibody responses. Since HIV vaccine-induced Th1 responses are considered important for a successful HIV vaccine, these data suggest that chronic helminthiasis may impact negatively on future HIV vaccination outcomes in adolescents living in SSA where helminthic parasites are endemic.